Association of Histological Findings with Tc-99m Sestamibi Parathyroid Imaging in Hyperfunctional Parathyroid Gland (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Hyperthyroidism is a relatively common disorder that results from increased production of parathormone. Tc-99m sestamibi (MIBI) scanning is used for localization of abnormal parathyroid gland, with high reported sensitivities. However, there exists a group of patients in whom MIBI scan is either equivocal or negative. Objectives: The aim of this study was to see association of the histological features of pathologic parathyroid gland with MIBI scan in hyperfunctional parathyroid gland. Methodology: This retrospective study was conducted with primary hyperthyroidism who underwent MIBI scan. The data were collected from the record from January 2012 to December 2014 for a period of two years. All patients underwent parathyroid surgery followed by histopathological examination. According to oxyphil cell distribution patients are divided in three groups. Group I comprised of >25.0% oxyphil cell; group II included the 25 to 75% oxyphil cell and group III included >75% of oxyphil cell. Result: A total 56 patients with hypercalcaemia and high serum parathyroid hormone (PTH) level were studied. Mean age was 41.3(±19.8) years with a range of 21 to 63 years. MIBI scan was true positive in 34(60.7%) cases and false negative in 22(39.3%) cases. In group I MIBI scan was true positive in 4(36.3%) cases and false negative in 7(63.7%) cases. In group II MIBI scan showed positive in 17(62.9%) cases and negative in 10(37.1%) cases. In group III out of 18 patients 13(72.2%) showed MIBI scan positive whereas, 5(27.8%) showed negative scan. The sensitivity was 36.3% in group I whereas, 62.9% and 72.2% in group II and group III respectively. Conclusion: Based on these findings, it could be say that Tc99m setamibi uptake correlate with parathyroid oxyphil cell content, and false negative scan can occur with parathyroid glands containing predominantly clear cell.Journal of National Institute of Neurosciences Bangladesh, 2016;2(1):14-18